Approaches to Forming the Attitude of Takzeem keuguree in Aceh Traditional Islamic Boarding School - Fahmi Arfan; Abubakar Abubakar; Ida Hasanah; Irwan Irwan; Muhammad Nur; T Makmur; Anwar Anwar; Rahmad Munazir (Universitas Serambi Mekkah, 2022)
The progress of a nation is determined by its human resources, the development of resources is closely related to the education process as stated in Sisdiknas Law No. 20 year 2003. The education system and learning system have an important contribution in building human resources and are interrelated with each other. Traditional Islamic boarding schools have a significant contribution in shaping the nation's character, although the learning objectives are closely related to the ownership of the institution, there are no certain requirements for educational participants. The traditional pesantren, often referred to as the dayah, is the only popular religious education system in Aceh. Dayah alumni are known for their docile attitude that has high empathy, often called takzeem, with this strong takzeem value, alumni are very easy to mobilize for the benefit of developing resources, and they are often used for political purposes in the era of regional elections. Therefore, this study aims to find out how to learn the values of takzeen keuguree in traditional Islamic boarding schools in Aceh Province. This research is qualitative involving technique-Data-Gathering, In-depth-interview, observation and documentation. The results of the study show that there are several approaches to Building Knowledge as a source of human behavior based on knowledge and the teacher, Tsawab Tarhib and Targhib approaches, Kuawalat/against guree and special learning for learning the attitude of takzim keuguree. Keywords :takzeem keuguree, tsawab, traditional Islamic boarding school